Low fat channa spread from filled milk - Yadav, Shilesh Kumar; Rani, Rekha; Singh, Bhopal; Thompkinson, DK (Indian Journal of Dairy Science, 2019)
There are mainly two types of spreads available in the domestic market - butter and cheese spread and both are high fat products. In present scenario most consumers are fat conscious and hesitant to consume butter fat because of the possibility of coronary heart disease. The dairy industry is constantly looking for alternative product to create a new category of modified spread. Peanut which is rich in protein and low in cholesterol have been used to offer new options to the consumers. For preparation of filled milk channa spread, peanut milk was prepared by soaking the roasted peanut and extracting with grains water ratio of 1:8 and filtered to collect the resultant milk. Filled milk thus obtained was coagulated with 0.8% calcium + lactate at coagulation temperature of 70 oC. The filled milk channa was then used for preparation of acceptable quality of table spread. Sensory attributes showed that filled milk channa spread scored for colour and appearance (8.1), flavour and taste (8.22), body and texture (7.54), spreadability (8.50) and for the overall acceptability (8.25). This prepared filled milk channa spread was better than commercially available spread used as control. The resultant spread was found to contain total solids 54.74%, fat 40%, protein 4.95%, carbohydrate 2.26%, ash 5.53%, salt 2%, acidity 0.34% LA and pH 5.6. Microbiologically the standard plate count was 6´103 cfu/g whereas, yeast and mold and coliform count were found to be absent.